Rada Sądownictwa Republiki Litewskiej - Balicki, Ryszard; Juškevičiūtė-Vilienė, Agne (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article analyses the political position, composition, organisation and competence of the Judicial Council in the Republic of Lithuania. It is a constitutional body guarding the independence of the institution responsible for the selection and promotion of judges. The purpose of this text is to present the principles of the institution’s functioning and evolution of its inclusion in the legal system of the Republic of Lithuania.
Keywords: Lithuania; Judicial Council; judicial power; judge; authority; constitution